2015
DOI: 10.3390/ijerph120606197
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation, and Hygiene in Schools in Low Socio-Economic Regions in Nicaragua: A Cross-Sectional Survey

Abstract: Water, sanitation, and hygiene (WaSH) in schools contributes to better health and educational outcomes among school-aged children. In 2012, UNICEF Nicaragua and partners conducted a cross-sectional survey of WaSH in 526 schools in 12 low socio-economic status municipalities in Nicaragua. The survey gathered information on: school characteristics; teacher and community participation; water and sanitation infrastructure; and hygiene education and habits. Survey results were analyzed for associations between vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 30 publications
8
57
0
2
Order By: Relevance
“…10 A crosssectional survey, conducted in schools in Nicaragua, showed that self-reporting of handwashing practice produced higher rates than those observed practices. 11 Conversely, effective hygiene promotion and practice in schools can be severely affected by the level of knowledge and attitudes learners have. Hygiene behaviors and practices are only made possible through a combination of hygiene education, water, sanitation and hygiene, as well as suitable facilities.…”
mentioning
confidence: 99%
“…10 A crosssectional survey, conducted in schools in Nicaragua, showed that self-reporting of handwashing practice produced higher rates than those observed practices. 11 Conversely, effective hygiene promotion and practice in schools can be severely affected by the level of knowledge and attitudes learners have. Hygiene behaviors and practices are only made possible through a combination of hygiene education, water, sanitation and hygiene, as well as suitable facilities.…”
mentioning
confidence: 99%
“…C'est une situation récurrente dans de nombreux pays, mise en évidence dans des études réalisées au Zimbabwe (Chikoore et al, 2011), au Togo (Gnazou et al, 2015), aux Etats Unis (Kenney et al, 2016), et en Zambie (Trinies et al, 2016). L'indisponibilité de l'eau contraint les équipes pédagogiques à développer des alternatives telles que la collecte de l'eau à l'extérieur des établissements réduisant ainsi, le temps réservé aux enseignements (Tamas et al, 2011et Jordanova et al, 2015, et affectant en plus, le taux d'absentéisme comme Pial et al, J. Appl. Biosci.…”
Section: Discussion Et Conclusionunclassified
“…The infrastructure development using the Public-Private Partnership (PPP) approach for the provision of water, sanitation has been discussed in an integrated manner with ISTEcS 2019 health program [4][5][6][7]. The PPP approach for water and sanitation is developed from some tools from other infrastructure development such as sector electricity, port, rail transportation, and tourism.…”
Section: Introductionmentioning
confidence: 99%